Glucose Intolerance and Cardiometabolic Risk in Adolescents Exposed to Maternal Gestational Diabetes: A 15-year follow-up study - Tam, Wing Hung (American Diabetes Association, 2010)
OBJECTIVE: Adolescent offspring of women with a history of gestational diabetes (GD) were evaluated for their cardiometabolic risks at a mean age of 15 years. RESEARCH DESIGN AND METHODS: One hundred and twenty-nine adolescents who were assessed for their cardiometabolic risks at 8 years of age were reassessed at 15 years of age. RESULTS: Adolescent offspring of mothers with GD had similar blood pressure, plasma lipid profile, and a rate of abnormal glucose tolerance as control subjects. In utero hyperinsulinemia was associated with a 17-fold increase in metabolic syndrome and a 10-fold increase in overweight at adolescence, independent of birth weight, Tanner stage, maternal GD status, and mother's BMI. CONCLUSIONS: In utero environment of hyperinsulinemia, irrespective of the degree of maternal GD, was associated with increased risk of overweight and metabolic syndrome during early adolescence in the offspring.